ASSESSMENT OF FLASH FLOOD HAZARD POTENTIAL IN A SMALL MOUNTAINOUS CIKUNDUL WATERSHED IN CIANJUR, WEST JAVA, INDONESIA - Kusratmoko, Eko; Septina, Armila Rista; Falensky, Muhammad Attorik (Ikatan Geografi Indonesia, 2024)
Flash flood is a geomorphic hazard that can cause huge losses in a short period of time. Cianjur regency, especially Cikundul Watershed is a flash flood frequent area. Therefore, flash flood potential mapping is needed to reduce the threat that can be caused by flash flood. In the flash flood potential mapping, Flash Flood Potential Index (FFPI) method is still rarely applied in Indonesia. This study aims to see the comparison of flash flood potential areas based on models developed in the FFPI method which is Smith, Brewster, Krudzlo, and Ceru models. The four models used slope, land use, soil texture, and vegetation cover as variables. Spatial analysis and statistical test was implemented to validate the flash flood potential areas with flash flood affected locations. The result reveals that Cikundul Watershed was dominated by moderate potential areas based on Brewster, Krudzlo, and Ceru model but low by Smith model. The result also reveals that 65% of 68 Sub-Sub Watershed have different potential and 35% have same potential. High potential areas in all four models was distributed in the Upper Cikundul Watershed. The Crosstab Fit Test result shows that Smith model is the closest model to the actual event.